2022
DOI: 10.3390/mi13040531
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Vibration Control Using Magnetorheological Damping Clamps under Fuzzy–PID Control Algorithm

Abstract: Aiming at the problem of low-frequency vibration of the hydraulic pipeline, a new type of semi-active damping magnetorheological (MR) damping clamp structure is designed. The structure size and material of the MR damping clamp were determined. The control model of the vibration damping system was established, and the control method combining fuzzy control and Proportional-Integral-Derivative (PID) control was used to carry out the numerical simulation, which proved that the fuzzy–PID control algorithm is effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The structure of the two-dimensional MRD pipe clamp is illustrated as Figure 1(a), which is mainly composed of two MRF dampers, inner pipe clamp, displacement sensor, DSP controller, current driver, power module, and adapter (Gong et al, 2022). The detailed structure of MR damper is shown in Figure 1(b).…”
Section: Modeling Of Mechanical Systemmentioning
confidence: 99%
“…The structure of the two-dimensional MRD pipe clamp is illustrated as Figure 1(a), which is mainly composed of two MRF dampers, inner pipe clamp, displacement sensor, DSP controller, current driver, power module, and adapter (Gong et al, 2022). The detailed structure of MR damper is shown in Figure 1(b).…”
Section: Modeling Of Mechanical Systemmentioning
confidence: 99%
“…Ji et al (2020) presented an approach to using MR technology to control pipeline vibration, and they experimentally demonstrated that the MR damper can effectively reduce pipeline vibration from 1 to 10 Hz when used with three semi-active control algorithms. Gong et al (2022) designed a new MR damping clamp, and the experimental results showed that the device has a good suppression effect on the low frequency vibration of hydraulic pipes. However, there are few studies on MR dampers for medium-high frequency vibration reduction in pipelines.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the main methods to reduce pipeline vibration included optimizing the structure of the pipeline system (Bi and Hao, 2016; Jia et al, 2015), reducing fluid excitation (Wang et al, 2017), and installing damping devices (Gong et al, 2022; Khazaee et al, 2020). The first two measures require significant modifications to the pipeline, and considering the complex structures of industrial pipelines, installing damping devices on the pipeline is an economical and practical vibration reduction scheme.…”
Section: Introductionmentioning
confidence: 99%